f(x)=7x+1, entao f(12)-f(9)/3 é igual a???
Soluções para a tarefa
Respondido por
3
f(12) = 7.12 + 1 = 84 + 1 = 85
f(9) = 7.9 + 1 = 63 + 1 = 64
![\frac{f(12)-f(9)}{3} = \frac{85-64}{3} = \frac{21}{3} = 7 \frac{f(12)-f(9)}{3} = \frac{85-64}{3} = \frac{21}{3} = 7](https://tex.z-dn.net/?f=+%5Cfrac%7Bf%2812%29-f%289%29%7D%7B3%7D+%3D++%5Cfrac%7B85-64%7D%7B3%7D+%3D++%5Cfrac%7B21%7D%7B3%7D+%3D+7)
f(9) = 7.9 + 1 = 63 + 1 = 64
bebel24:
poh vlw msm
Perguntas interessantes
Inglês,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás